MOCAT2: a metagenomic assembly, annotation and profiling framework - Kultima, Jens Roat; Coelho, Luis Pedro; Forslund, Kristoffer; Huerta-Cepas, Jaime; Li, Simone S.; Driessen, Marja; Voigt, Anita Yvonne; Zeller, Georg; Sunagawa, Shinichi; Bork, Peer (Bioinformatics, 2016)
Abstract. Summary: MOCAT2 is a software pipeline for metagenomic sequence assembly and gene prediction with novel features for taxonomic and functional abundan